This preview shows page 1. Sign up to view the full content.
Unformatted text preview: ll.
Now, go back to the radical and then use the second and first property of radicals as we did in the
first example. 18 x 6 y11 = 9 ( x3 ) 2 ( y ) (2y) =
52 9 (x ) ( y )
32 52 2 y = 3x3 y 5 2 y Note that we used the fact that the second property can be expanded out to as many terms as we
have in the product under the radical. Also, don’t get excited that there are no x’s under the
radical in the final answer. This will happen on occasion.
[Return to Problems] (d) 4 32 x9 y 5 z12
This one is similar to the previous part except the index is now a 4. So, instead of get perfect
squares we want powers of 4. This time we will combine the work in the previous part into one
step.
4 32 x9 y 5 z12 = 4 16 x8 y 4 z12 ( 2 xy ) = 4 16 4 ( x 2 ) 4 4 y4 4 ( z3 ) 4 4 2 xy = 2 x 2 y z 3 4 2 xy
[Return to Problems] (e) 5 x12 y 4 z 24
Again this one is similar to the previous two parts.
5 x12 y 4 z 24 = 5 x10 z 20 ( x 2 y 4 z 4 ) = 5 (x ) (z )
2 55 4 55 x2 y 4 z 4 = x2 z 4 5 x2 y 4 z 4 In this case don’t get exci...
View Full
Document
 Spring '12
 MrVinh

Click to edit the document details